2015
DOI: 10.1039/c5sc01307k
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of pH-dependent electrostatic catalysis of radical reactions

Abstract: Fluorescence spectroscopy demonstrated pH-dependent electrostatic effects on the kinetics and thermodynamics of hydrogen atom transfer between 1-hydroxy-2,2,6,6-tetramethyl-4-piperidinecarboxylic acid and {2,2,6,6-tetramethyl-4-[(7-nitro-2,1,3-benzoxadiazol-4-yl)amino]-1-piperidinyl}oxidanyl radical in dichloromethane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
75
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 17 publications
4
75
0
Order By: Relevance
“…31 Coote et al have also reported using pH switchable elds that rely on protonationdeprotonation to vary radical stability. 32 Our efforts to generate controllable and directional internal electric elds have focused on installation of non-redox active cations proximal to redox-active reaction sites. We rst reported the cobalt derivatives of the salen-crown complex shown in Chart 1.…”
Section: Introductionmentioning
confidence: 99%
“…31 Coote et al have also reported using pH switchable elds that rely on protonationdeprotonation to vary radical stability. 32 Our efforts to generate controllable and directional internal electric elds have focused on installation of non-redox active cations proximal to redox-active reaction sites. We rst reported the cobalt derivatives of the salen-crown complex shown in Chart 1.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments have shown that this can be achieved at the nanoscale using scanning tunneling microscopy, 4,5 and, at larger scales, using electrodes 6 charged insulators, 7 charged functional groups, [8][9][10] and metal ions. [11][12][13] While catalysis has been the main focus until now, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] perhaps the most interesting applications stem from the ability of electric fields to change outcome of a reaction. For instance, theoretical studies have shown that the regio-and stereoselectivity of a Diels-Alder reaction can be changed with either external oriented fields 16,17 or appropriately placed charged functional groups.…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] In a subsequent but related study, the same authors used this platform of pointcharges to demonstrate a pH switch to control the rate of hydrogen atom transfer between nitroxides and hydroxylamines. [19] Herein, instead of relying on pH changes to introduce local point-charges in a molecule, we have explored the alternative of creating localized cations using electroactive redox groups and an electron sink/source (i. e., an electrified interface). To this goal we synthesized a molecule containing two separate redox units, ferrocene and TEMPO, linked by a spacer.…”
Section: Introductionmentioning
confidence: 99%